Qualitative characterization of skin tissue with dynamic laser speckle - Gonzalez, Mariela Azul (2019)
This work presents a preliminary study for the effective characterization of the skin tissue surface by means of Dynamic Laser Speckle. Although dermoscopy is widely used to perform this analysis, Dynamic Laser Speckle was applied as a complementary technique for skin assessment, aimed to help medical diagnosis by giving additional information regarding texture patterns and microcirculation profiles. Due to the nature of the underlying phenomena, the study of the temporal evolution of speckle diagrams provides an interesting non-destructive and non-invasive tool to characterize microtexture changes in the skin, reflecting physiological variations contained in sample activity over time. This analysis will assist the characterization of normal skin tissue, enabling the establishment of qualitative comparisons with ongoing skin diseases and to treatments monitoring. The skin microcirculation profile after a pressure protocol was assessed in healthy skin, to achieve a qualitative measure of the reperfusion based on dynamic speckle activity. The applied methodology is based on a multi-descriptor approach after a Self-Organizing Map segmentation process.